WEB-BASED SYSTEM FOR RADIOLOGICAL PROTECTION PROGRAMS: A REPOSITORY FOR RESEARCH, CONSULTATION AND INFORMATION (Brazilian Journal of Radiation Sciences (BJRS), 2015)
In order to establish a Radiation Protection Plan or a Radiation Emergency Plan, Brazilian facilities should take into account all procedures based on national and international guidelines and recommendations. This information can be found in several documents published by different organizations over the past decades: the International Commission on Radiological Protection (ICRP), International Atomic Energy Agency (IAEA) and Comissão Nacional de Energia Nuclear (CNEN). Therefore, this project aims the informatization of the radiological protection programs in a single system in order to offer unified programs and inter-related information in Portuguese, providing Brazilian facilities a complete repository for research, consultation and information, combining computer technology and radiological protection in order to enhance the best benefits from information technology. This research work includes programs about: (1) Monitoring of Workplace  (Monitoring for External Radiation, Monitoring for Surface Contamination, Monitoring for Air Contamination) and (2) Individual Monitoring  (Monitoring of External Exposure and Monitoring of Internal Exposure, Monitoring for Skin and Clothing). WEB platform tools and functionalities were developed according to target public needs, regarding new possibilities of media, mobile access, and information sharing. The servers processing power added to the technology of relational databases allow to integrate information from different sources, enabling complex queries with reduced response time. Moreover, taking into account this is a pioneer project with the prospect of long-term use, the challenge involves the combination of multiple computer technologies that allows a robust, effective and flexible system, which can be easily adapted to future technological innovations.